Cutaneous and subcutaneous metastases from bladder carcinoma - Dirican, Ahmet; Küçükzeybek, Yüksel; SomalI, Ișıl; Erten, Çiğdem; Demir, LütfIye; Can, Alper; Bayoğlu, İbrahim Vedat; Ermete, Murat; Aksoy AltInboğa, Ayşegül; Tarhan, Mustafa Oktay (Contemporary Oncology/Współczesna Onkologia, 2012)
Cutaneous metastases of bladder carcinoma are very rare. The rate of cutaneous metastasis in urologic malignancies is 1.3% and this rate was found to be 0.84% for bladder carcinomas. Cutaneous metastasis of bladder carcinoma can be confused with cellulitis. This case report presents a 60-year-old patient operated on for bladder carcinoma and undergoing treatment for cellulitis because of erythematous lesions appearing in the suprapubic region in the early postoperative period. As there was no response to antibiotic treatment, skin biopsy was performed and cutaneous metastasis was diagnosed. Subsequently, chemotherapy with carboplatin and gemcitabine was started. The prognosis of bladder carcinoma with cutaneous metastasis has been reported to be poor.